DIGITAL ECONOMIC & FINANCIAL INCLUSION FOR ECONOMIC RECOVERY IN INDONESIA - Rudi Santoso; Martinus Sony Erstiawan; Tony Soebijono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The research focuses on economic recovery strategies by utilizing the digital economy and financial inclusion. The basic postulate in this research is an empirical study showing an increase in the digital economy during a pandemic. This resulted in the use of financial inclusion increasing significantly. So that both are the biggest variables in post-pandemic economic recovery. The digital economy and financial inclusion are driving forces in national economic recovery. The basic assumption of this research refers to access to formal financial services, which increases the ability to drive micro-economy. The output of this research is a model of an elastic national economic recovery strategy using digital platform business and financial inclusion. The model developed in this study offers an inclusive financial access strategy in the digital economy sector to drive microeconomics. With the movement of microeconomics, the acceleration of post-pandemic economic recovery will be more effective. As an indicator of success, the objects used in this research are start-up growth and digital-based financial access. In addition, the aspects used as benchmarks for success in this model are: Governance, People, and Financial & Economic.